B7-H3 and CSPG4 co-targeting as Pan-CAR-T cell treatment of triple-negative breast cancer - Siobhán O’Connor; Barbara Savoldo; Gianpietro Dotti; Simone Stucchi; Roberto Borea; Susana Garcia-Recio; Manuela Zingarelli; Patrick D Rädler; Elena Camerini; Caroline Marnata Pellegry; H Shelton Earp; Lisa A Carey; et al. (Journal for ImmunoTherapy of Cancer)
Purpose Chimeric antigen receptor T (CAR-T) cell therapy is under clinical investigation in patients with metastatic triple-negative breast cancer (TNBC). However, the identification of targetable antigens remains a high priority to avoid toxicity and prevent tumor escape.Experimental design Here we analyzed the gene expression of B7-H3 (CD276) and chondroitin sulfate proteoglycan 4 (CSPG4) in 98 TNBC samples identified in the AURORA US Network and Rapid Autopsy RNA sequencing data set at University of North Carolina (UNC). We then performed immunohistochemistry analysis for B7-H3 and CSPG4 protein expression in 151 TNBC samples collected at UNC. Finally, the validity of the proposed B7-H3 and CSGP4 co-targeting was tested in clinically relevant TNBC patient derived xenograft (PDX) models.Results We observed that CD276 and CSPG4 genes are broadly and comparably expressed in TNBC samples, and gene expression is generally conserved in tumor metastases. None of the TNBC analyzed met the criteria for simultaneous low expression of CSPG4 and CD276 genes. Immunohistochemistry analysis showed a median H-score of 138 (105–168, lower and upper quartile, respectively) for B7-H3 expression and a median H-score of 33 (14–78 lower and upper quartile, respectively) for CSPG4 expression. Notably, 49% of the TNBC cores with B7-H3 H-score ≤105 exhibited a CSPG4 H-score exceeding its median value, and 37% and 18% of the TNBC cores with low B7-H3 expression scored CSPG4 expression above its median H-score or exceeded its upper quartile, respectively, confirming that at least one of these two proteins is expressed in 94% of the analyzed tumors. Finally, optimized dual-specific B7-H3 and CSPG4 CAR-T cells eradicated tumors with mixed antigen expression in TNBC PDX models.Conclusions These data highlight the clinical potential of the proposed approach that could be applicable to the great majority of patients with TNBC as well as most of patients with breast cancer in general.